2011
DOI: 10.4161/auto.7.11.16658
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid induces autophagy through p53/AMPK/mTOR signaling and promotes apoptosis in human cancer cells harboring wild-type p53

Abstract: Docosahexaenoic acid (DHA) has been reported to induce tumor cell death by apoptosis. However, little is known about the effects of DHA on autophagy, another complex well-programmed process characterized by the sequestration of cytoplasmic material within autophagosomes. Here, we show that DHA increased both the level of microtubule-associated protein light-chain 3 and the number of autophagic vacuoles without impairing autophagic vesicle turnover, indicating that DHA induces not only apoptosis but also autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
139
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 44 publications
(61 reference statements)
15
139
1
Order By: Relevance
“…Despite the reports of autophagic cell death (18,35,36) and autophagy-dependent antitumor immune response (37), the fundamental role of autophagy is thought to be cytoprotection under starvation and stress conditions (16). Many reports suggest that autophagy functions cytoprotectively in cancer cells (19,20,36,38). In line with this, we previously reported that autophagy protects against apoptosis in human prostate and breast cancer cells after treatment with an innate adjuvant receptor ligand (21,22).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Despite the reports of autophagic cell death (18,35,36) and autophagy-dependent antitumor immune response (37), the fundamental role of autophagy is thought to be cytoprotection under starvation and stress conditions (16). Many reports suggest that autophagy functions cytoprotectively in cancer cells (19,20,36,38). In line with this, we previously reported that autophagy protects against apoptosis in human prostate and breast cancer cells after treatment with an innate adjuvant receptor ligand (21,22).…”
Section: Discussionmentioning
confidence: 48%
“…Autophagy has received much attention in various cell biology fields (16,17). Despite the reports of autophagic cell death (18,35,36) and autophagy-dependent antitumor immune response (37), the fundamental role of autophagy is thought to be cytoprotection under starvation and stress conditions (16). Many reports suggest that autophagy functions cytoprotectively in cancer cells (19,20,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several reports have suggested a change in autophagy in cancer cell lines that are sensitive and display cytotoxic and/or cytostatic responses to physiological doses of PUFAs. [48][49][50][51][52][53] We explore whether increased autophagy is a part of the cellular response to PUFAs also in spontaneously arising ARPE-19 cells. If so, we hypothesize a correlation between the disease preventive effects of n-3 PUFAs and stimulation of autophagy in retinal pigment epithelial cells where the initial phases of AMD occurs.…”
Section: Introductionmentioning
confidence: 99%
“…p53 inhibits mTOR by activation of AMP-activated protein kinase (AMPK) and subsequent regulation of the TSC1/TSC2 complex (21). Inactivation of either TSC1/TSC2 complex or AMPK inhibits the impact of p53 on mTOR pathway (21).…”
mentioning
confidence: 99%